Intrauterine Bowel Rupture of Fetus from Stab Wound Injury in a Pregnant Woman: A Case- Report - Ebrahimi, Atefeh; Rezaei Aliabad, Nahid; Parsa, Yekta (Novelty in Biomedicine, 2021)
Background: Penetrating injuries of the uterus are rare complications during pregnancy which happen most by stab and gunshot wounds. Although the fetus is enclosed within the protective shield of the uterus, it is vulnerable to forceful trauma to the maternal abdomen. Cases Report: Following an upper abdominal stab wound to the 18-week pregnant mother, fetal death had occurred in the uterine. She was resuscitated and underwent exploratory laparotomy and hysterotomy. The patient had a 3cm laceration on the upper anterior fundus, which has caused the rupture of membrane, leading to fetal death and protruding of bowel loops. After surgery, she was transformed into the recovery room with stable hemodynamic status. Conclusion: Trauma during pregnancy is a significant burden due to morbidity and mortality that follows mother and fetus for developed countries. The ultimate purpose is to provide optimal care for a mother and fetus.